Phytochemicals Dietary Sources, Innovative Extraction and Health Benefits - Aguilera Gutiérrez, Yolanda; Benítez García, Vanesa (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Phytochemicals, consumed as part of the diet, improve human health by lowering its risk and preventing chronic diseases. Fruits, vegetables, chocolate, pulses, and teas, among others, are rich sources of phytochemicals; however, only a certain amount has been isolated and identified. Moreover, the wide diversity of these compounds requires optimized extraction methodologies for further characterization and evaluation of healthy properties. This Special Issue addresses interdisciplinary research related to phytochemicals, highlighting their dietary sources, innovative extraction methodologies, and their effects on human health. Seven papers have been selected for further contribution to phytochemical studies.